Peak fat oxidation during submaximal exercise remains consistent across menstrual cycle and combined oral contraceptive phases - Löfberg, I. E.; Karppinen, J. E.; Laatikainen-Raussi, I.; Ihalainen, J. K.; Lehti, M.; Hackney, A. C.; Mikkonen, R. S. (Medicine & Science in Sports & Exercise, 2025)
Purpose Substrate metabolism during exercise may vary across the menstrual cycle (MC) phases, likely due to estradiol (E2) and progesterone (P4). This study examined substrate metabolism during exercise in naturally menstruating (NoOC, n = 34) and women using combined oral contraceptives (COC, n = 19).